Care at the office of pediatric gynecology - González, Carmen (2015)
OBJECTIVE: To determine the characteristics of the attention of the Office of Pediatric Gynecology. DESIGN: Observational, retrospective study. MATERIALS AND METHODS: Review of cases on the basis of HIS attention leaves the Clinic of Pediatric Gynecology Cayetano Heredia National Hospital (HNCH) for the years 1998 and 1999. RESULTS: 15 infants, 127 preschool and 213: 355 patients were found school. Three doctors performed 95% of the care and 80% of the patients came from the area of influence of HNCH Vulvovaginitis was diagnosed in 75.5% of patients and genital bleeding in 18.3%. Conclusion: The vulvovaginitis and genital bleeding are the leading cause of any pediatric gynecologist age.